Identifying dimensions of fatigue in haemodialysis important to patients, caregivers and health professionals: An international survey - Ju, Angela; Unruh, Mark; Davison, Sara N.; Dapueto, Juan; Dew, Mary A.; Fluck, Richard; Germain, Michael; Jassal, Sarbjit V.; Obrador, Gregorio; O'Donoghue, Donal J.; Howell, Martin; O'Lone, Emma; et al. (My University, 2019)
Background: Patient-reported outcome measures of fatigue used in research in haemodialysis vary widely in the dimensions assessed; and the importance of these dimensions to patients and health professionals is unknown. This study aimed to identify the most important dimensions of fatigue to assess in patients on haemodialysis participating in trials. Methods: In an international survey, patients/caregivers and health professionals rated the absolute and relative importance of content and measurement dimensions to include in a core outcome measure of fatigue. A 9-point Likert scale (7-9 indicating critical importance) was used to assess absolute importance and best-worst scale was used to assess importance of each dimension compared to others. © 2019 Asian Pacific Society of Nephrology.
Keywords: Fatigue; Haemodialysis; Patient-reported outcome measures